Influence of Gender on Recreational Participation. A Critical Literature Review - Kamau, Roselyn Wanja (Journal of Modern Hospitality, 2022)
Purpose: Recreation is an intentional activity geared towards accomplishment of self and social gains including refurbishment and collective connectivity. The overall objective of this study was to examine influence of gender on recreational participation. A critical literature review Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: Music followed by singing and dancing while the least popular indoor recreational activity was aerobics and snooker/pool. The most popular outdoor recreational activity was walking while the least popular outdoor recreational activity for women was swimming and playing cards. Frequency of participation in both indoor and outdoor recreational activities by women was influenced by the age. Frequency of participation in both indoor and outdoor recreational activities was not influenced by the family size or the number of children. Frequency of participation in the indoor and outdoor recreational activities by women was not influenced by their monthly income. The family size was not a determining factor for participation in both indoor and outdoor recreational activities Unique Contribution to Theory, Policy and Practice: This study recommended that the county government should set aside land for developing various recreational facilities within the informal settlement areas to be accessed by all residents to mitigate time constraints; for example, construction of swimming pools since swimming is reported as the least popular outdoor activity.